Determinan wakaf tunai di kalangan milenial - Setiyowati, Supami Wahyu; Slamet, Slamet; Rofiq, Aunur (Jurnal Ekonomi Modernisasi, 2023)
The purpose of this study was to examine the effects of critical factors that influence cash waqf. This study is quantitative. The population is 2021 alumni of the Faculty of Economics and Business who are Muslim. The sampling technique was based on the criteria totaling 227 alumni. The data analysis technique used smart-PLS. The results showed that knowledge, belief, and religiosity had a positive effect on attitudes. Attitudes and subjective norms did not affect cash waqf. Behavior, intention, and awareness affected cash waqf. The implication of this study is the need for socialization of waqf among the general public. Encouragement from the family of ulama and the workplace are needed to carry out cash waqf.